Simulations of high speed, low angle, structural impacts with water. - Papagiannis, Lampros (Cranfield University, 2016)
The improvement of the numerical capabilities of predicting the structural loading of high speed, low angle impacts, such as an aircraft during ditching, is addressed in this thesis. Research into the phenomenon of ditching, has shown that specific flow phenomena occur, which influence the structural loading of the aircraft as well as its general dynamics. These phenomena are cavitation, suction and the presence of air. The simple water model that is used in vertical simulations does not provide accurate enough predictions, when considering impacts characterised by high forward velocities. The meshless Smoothed Particle Hydrodynamics (SPH) method, known for its ability to model large deformations, was enhanced with the addition of cavitation and aeration, in order to improve the fluid model used for fluid-structure interactions with forward velocities, such as ditching. With the use of a homogeneous mixture model, a more realistic transient cavitation model was implemented, considering the presence of vapour nuclei in the fluid. It considered the vapour pressure, the growth and reduction evolution of the phenomenon with the use of the Rayleigh-Plesset equation and the change in the properties of the fluid. Initial 2D investigation captured the phenomenon and compared well with published results. Further investigation of plate impacts showed the sensitivity of the approach on the number of nuclei present in the fluid, as well as the influence of the boundary and the potential wave reflection interference on the free surface. The presence of air in the water model was implemented with a mixture approach, governed by the change of the properties of the air. Investigation of plate impacts and a fuselage section showed that the pressures decrease, according to theory, with increasing levels of aeration. In the case of the fuselage section, the results showed little influence in the overall behaviour and highlighted the importance of the phenomenon of suction. Finally, the numerical investigation of ricochet, a phenomenon also characterised by high forward velocities and with available experimental results, was considered as a means of assessing the overall capabilities of the SPH method. Sphere and cylinder results compared favourably for the lower velocity impacts but proved inaccurate for the higher velocities range. This was attributed to a lower deceleration experienced by the projectiles combined with a frictionless contact. The computational cost of such simulations was also considered prohibitive for further investigation within this project.
PhD in Aerospace
Keywords: Ditching; cavitation; aeration; fluid-structure interaction; SPH; ricochet